IMPLEMENTATION OF PSAK 412 WAQF ACCOUNTING AND FINANCIAL STATEMENTS AT WAQF MULIA INSTITUTE - Ibnu Hajar; Suciyanti Suciyanti (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study critically evaluates the implementation of PSAK 412 (Waqf Accounting Standard) by a national-scale nazhir, the Waqf Mulia Institute (WMI), focusing on achieving substantial transparency and accountability in waqf asset management. Employing a qualitative, holistic single case study design, the research analyzed WMI's 2023–2024 financial statements and primary data from management interviews, comparing their practices against the four pillars of PSAK 412: Recognition, Measurement, Presentation, and Disclosure. Findings reveal high compliance in Presentation and Disclosure, with WMI providing all five mandatory financial statements comprehensively; however, a significant implementation gap exists in Measurement. Despite management's claim of using fair value, evidence—such as a nil value in the